Pengaruh Safety dan on Time Performance Terhadap Loyalitas Pelanggan (Studi Kasus Pada Maskapai Batik Air) - Widiyarini, Widiyarini; Johan, Ria Susanti; Septariani, Desy; Asikin, Iin (Peneliti.net, 2023)
Safety is an important aspect in national aviation services. Apart from that, the punctuality aspect is also a priority and an indicator of the success of airline services. The research method used is a quantitative method. The variables safety, timeliness and customer loyalty are the objects of this research. Data was taken through questionnaires and interviews as well as literature searches. The data was processed using classical assumption tests, validity, reliability, multiple regression and the F test. The results of the research show that there is a positive and significant influence between the Safety variable and Batik Air Airline Customer Loyalty. This research found that there is a positive and significant relationship between On Time Performance and Customer Loyalty of Garuda Indonesia Airlines. This means that with increasing On Time Performance, Batik Air Airline Customer Loyalty will also increase. There is a strong correlation between On Time Performance and Batik Air Customer Loyalty. There is a strong positive correlation between On Time Performance and Batik Air Customer Loyalty. There is a positive and significant influence of Safety and OnTime Performance on Customer Loyalty if considered together.